Factors Affecting Proximal Colon Cleansing Based on Bowel Movement Kinetics: A Prospective Observational Study. (3rd March 2019) - Kim, Dae Bum; Lee, Kang-Moon; Kang, Sung-Goo; Jung, Sung Hoon
Abstract : Background . Previous studies have suggested that relatively poor bowel preparation in the proximal colon, compared to that in the distal colon, could decrease the usefulness of colonoscopy. The aim of this study was to determine whether the "first defecation time" after polyethylene glycol (PEG) administration affects the cleansing quality in the proximal colon. Methods . A total of 425 individuals who were scheduled to undergo a screening colonoscopy were enrolled prospectively at the healthcare center of St. Vincent's Hospital, Suwon, Korea, between April 2015 and March 2016. Bowel cleansing was performed using 4 L of PEG. Surveys were conducted to obtain information regarding the "first defecation time." Endoscopists assessed the quality of bowel preparation in each bowel segment. Results . We investigated 425 consecutive eligible cases. The mean "first defecation time" after PEG administration was 54.35 min. The quality of bowel preparation was poorer in the proximal colon than that in the distal colon. The adequate (excellent, good) and inadequate (fair, poor) proximal colon preparation groups comprised 360 (84.7%) and 65 (15.3%) patients, respectively. A multivariate analysis revealed that female gender (P = 0.029 ), small waist circumference (P = 0.027 ), and the long "first defecation time" (P = 0.034 ) were independently associated with inadequate bowel preparation in the proximal colon. Conclusion . Our data document that the "first defecation time, " female gender, and a small waist circumference affect the quality of preparation in the proximal colon. Inadequate preparation in the proximal colon was more common in females. Patients with these factors undergoing colonoscopy should be monitored carefully.